2013
DOI: 10.1183/09059180.00008512
|View full text |Cite
|
Sign up to set email alerts
|

Ivacaftor treatment in patients with cystic fibrosis and the G551D-CFTR mutation

Abstract: Cystic fibrosis (CF) is an autosomal recessive lethal disease caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene that encodes for CFTR, an epithelial cell-surface expressed protein responsible for the transport of chloride (Cl -). Gating mutations associated with defective conductance can be modulated by CFTR potentiators.Ivacaftor is a CFTR potentiator approved for the treatment of CF patients .6 yrs of age with at least one copy of the G551D-CFTR mutation. Herein, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 26 publications
(44 reference statements)
1
31
0
1
Order By: Relevance
“…Similar effects with an overall improvement of FEV1 % pred of 12.5% were observed in younger CF patients (6-11 years of age) with a G551D mutation, and it was shown that ivacaftor improves the lung clearance index in children with CF with normal spirometry [64,66]. While it remains to be seen to what extent these therapeutic benefits on pulmonary function are cumulative to already existing symptomatic therapies [67][68][69][70], this breakthrough provides an important proof-of-concept that mutation-specific therapy is possible and may, therefore, mark the beginning of a new era of personalised medicine for CF, a topic that has been discussed in several recent reviews [71][72][73]. The CFTR potentiator creates opportunities for personalised medicine for CF However, because the G551D mutation affects only ,4% of CF patients worldwide, considerable challenges remain that need to be overcome before a larger group of patients can benefit from these novel CFTR modulator therapies.…”
Section: Emerging Novel Therapies To Rescue Mutant Cftr: Breakthroughmentioning
confidence: 99%
“…Similar effects with an overall improvement of FEV1 % pred of 12.5% were observed in younger CF patients (6-11 years of age) with a G551D mutation, and it was shown that ivacaftor improves the lung clearance index in children with CF with normal spirometry [64,66]. While it remains to be seen to what extent these therapeutic benefits on pulmonary function are cumulative to already existing symptomatic therapies [67][68][69][70], this breakthrough provides an important proof-of-concept that mutation-specific therapy is possible and may, therefore, mark the beginning of a new era of personalised medicine for CF, a topic that has been discussed in several recent reviews [71][72][73]. The CFTR potentiator creates opportunities for personalised medicine for CF However, because the G551D mutation affects only ,4% of CF patients worldwide, considerable challenges remain that need to be overcome before a larger group of patients can benefit from these novel CFTR modulator therapies.…”
Section: Emerging Novel Therapies To Rescue Mutant Cftr: Breakthroughmentioning
confidence: 99%
“…Taken together, these preclinical results suggest that ivacaftor specifically targets and repairs the underlying gating defect caused by the G551D mutation. Based on this evidence clinical trials were commenced in CF patients carrying at least one copy of the G551D-CFTR mutation, the results of which are discussed in the article by SERMET-GAUDELUS [55] [56,57].…”
Section: Cftr Correctorsmentioning
confidence: 99%
“…He will also comment on the various classes of CFTR mutations and how they can be targeted by CFTR modulators, as well as briefly examining the proposed mechanisms of action of CFTR modulators before focusing on the pre-clinical development of ivacaftor. SERMET-GAUDELUS [18] will explore the clinical translation of CFTR modulators by reviewing data from ivacaftor clinical trials in CF patients with a specific CFTR mutation called G551D, and conclude by commenting on the potential future impact of CFTR modulators on CF care.…”
Section: Cystic Fibrosis As a Paradigm For Prospective Personalised Dmentioning
confidence: 99%